2009
DOI: 10.1001/archneurol.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neuromyelitis Optica With Mycophenolate Mofetil

Abstract: Background: Neuromyelitis optica (NMO) is the first inflammatory autoimmune demyelinating disease of the central nervous system for which a specific antigenic target has been identified; the marker autoantibody NMO-IgG specifically recognizes the astrocytic water channel aquaporin 4. Current evidence strongly suggests that NMO-IgG may be pathogenic. Since disability accrues incrementally related to attacks, attack prevention with immunosuppressive therapy is the mainstay of preventing disability. Objective: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(212 citation statements)
references
References 38 publications
4
197
0
4
Order By: Relevance
“…In those with relapsing disease, lifelong therapy should be considered (2). Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…In those with relapsing disease, lifelong therapy should be considered (2). Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…MMF treatment for a median of 20-27 months resulted in a reduction of the ARR by 80-93 % and improvement of the median EDSS in 3/ 4 studies (not reported in 1). More than 90 % of patients had stable or improved disability [83,84], and 46-65 % were relapse-free [79,81,83,84]. Discontinuation rates due to disease activity or side effects were 15-25 %.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
“…It inhibits lymphocyte proliferation by suppression of guanosine nucleotide biosynthesis and is used for psoriasis, proliferative lupus nephritis, and renal transplant rejection. Four retrospective cohorts evaluating 24-58 patients with mostly AQP4-IgG-positive NMOSD have reported beneficial outcomes of MMF therapy with or without concomitant corticosteroids [79,81,83,84]. MMF treatment for a median of 20-27 months resulted in a reduction of the ARR by 80-93 % and improvement of the median EDSS in 3/ 4 studies (not reported in 1).…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of IVIG in the treatment of acute NMO has not been adequately studied. A variety of immunosuppressive drugs, including rituximab, mitoxantrone, mycophenolate mofetil (MMF), and azathioprine have been used to prevent relapses of NMO, but their effectiveness in the treatment of acute exacerbations is unknown [48][49][50][51][52].…”
Section: Neuromyelitis Opticamentioning
confidence: 99%